MATH SOLVE

3 months ago

Q:
# PLZ HELP! Need this DESPERATELY! Worth 15 points and will mark Brainliest! Thx so much :)

Accepted Solution

A:

Answer:Part 1) [tex]a^{b+2}=(x)(a^{2})[/tex]Part 2) [tex]2a^{3b}+a^{2b}+a^{b}=2x^{3}+x^{2}+x[/tex]Step-by-step explanation:Part 1) Given that [tex]a^{b}=x[/tex] evaluate the following[tex]a^{b+2}[/tex]we know that[tex]a^{b+2}=(a^{b})(a^{2})[/tex]Remember that when multiplying two powers that have the same base, you can add the exponents[tex]a^{b}=x[/tex]sosubstitute[tex]a^{b+2}=(x)(a^{2})[/tex]Part 2) Given that [tex]a^{b}=x[/tex] evaluate the following[tex]2a^{3b}+a^{2b}+a^{b}[/tex]we know that[tex]2a^{3b}+a^{2b}+a^{b}=2(a^{b})^{3}+(a^{b})^{2}+a^{b}[/tex]Remember that[tex]a^{b}=x[/tex]sosubstitute[tex]2a^{3b}+a^{2b}+a^{b}=2x^{3}+x^{2}+x[/tex]